Assessment of radiological risk for marine biota and human consumers of seafood in the coast of Qingdao, China. (September 2015) - Yang, Baolu; Ha, Yiming; Jin, Jing
Highlights: Activity concentrations of 226 Ra, 232 Th, 40 K and 137 Cs in seafood were determined. The radiation dose rate for marine biota was estimated. The committed effective dose and lifetime cancer risk for humans were estimated. Seafood in the present study is of no risk to public health. Abstract: This paper reports the levels of 226 Ra, 232 Th, 40 K and 137 Cs in the edible parts of 11 different marine species collected from the Qingdao coast of China. The activities of 226 Ra, 232 Th and 40 K ranged from 0.08 ± 0.03 to 1.65 ± 0.60 Bq kg −1 w.w., 0.09 ± 0.02 to 1.44 ± 0.10 Bq kg −1 w.w., 26.89 ± 1.25 to 219.25 ± 5.61 Bq kg −1 w.w., respectively. Artificial 137 Cs was undetectable or close to the detection limit in the biota sampled. To link radioactivity to possible impact on health, we calculated radiation doses to both the marine biota and human beings. We showed that doses in all cases were dominated by naturally occurring 40 K and that 137 Cs doses were negligible compared with 40 K-derived doses. The total doses to marine biota ranged between 16.55 and 62.41 nGy h −1 among different biota species, which were below the benchmark level of aquatic organism. The committed effective dose to humans through seafood consumption varied from 10.55 to 36.17 μSv y −1, and the associated lifetime cancer risks ranged from 5.93E−05 to 9.49E−05 for different age and gender groups. Both the dose and cancer risk to humans were at the acceptable range. Despite the significant amount of radionuclides released as a result of the Fukushima accident, their impact on the seafood in Qingdao coast appears to be negligible based on our measurements of concentrations of radionuclide activity and internal dose estimates.